"Lenormand et ses Fantômes" : a study of the playwright's work, 1914 to 1942 - Ranalli, Richard Gary (My University, 1969)
The purpose of this paper will be to analyse some of the forces that motivate the characters in Henry-Réné Lenormand's drama between 1914 and 1942 and to discuss their dramatic merit; subsequently an attempt will be made to relate our findings to the author's thought and personality and to account for the relative lack of attention that his work has undergone in recent years.
Keywords: French and Francophone Language and Literature; French and Francophone Language and Literature